Reconceptualizing Canadian Federal Political Culture: Examining Differences between Quebec and the Rest of Canada. Issue 1 (29th April 2019) - McGrane, David; Berdahl, Loleen
Abstract: While the concept of federal political culture has been attractive to federalism scholars, Canada has proved to be a puzzling case and generated contradictory results across studies. We test a new definition of Canadian federal political culture using original survey data and find that Canadians have moderate levels of federal political culture driven by a utopian view of federalism in which the promotion of diversity should be achieved without any negative consequences for the unity of the polity. We also find that Quebecers and other Canadians have similar levels of federal political culture and that the results are consistent when survey questions are altered to take out country-specific references.